2020
DOI: 10.7759/cureus.11643
|View full text |Cite
|
Sign up to set email alerts
|

Primary Psychiatric Disorder Masking the Diagnosis of Lupus Cerebritis

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that is known to affect different organs in the body. Nervous system involvement is common and can manifest as neurological or neuropsychiatric symptoms. A 23-year-old female with no significant past medical history, presented with nausea and vomiting for two weeks and unusual behavior for three days. Brain magnetic resonance imaging (MRI) showed small vessel ischemic changes and abnormal T2 flair/periventricular signal. Lab workup was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, headaches, anxiety, mood, and cognitive disorders are the most frequent neuropsychiatric manifestations of SLE. Cerebrovascular disease, neuropathies, acute confusional states, and seizure disorders are the most frequent manifestations associated with NPSLE, suggesting several pathogenetic mechanisms in NPSLE similar to our current understanding of the extracranial manifestations of SLE [ 6 , 15 , 16 ].…”
Section: Reviewmentioning
confidence: 75%
“…However, headaches, anxiety, mood, and cognitive disorders are the most frequent neuropsychiatric manifestations of SLE. Cerebrovascular disease, neuropathies, acute confusional states, and seizure disorders are the most frequent manifestations associated with NPSLE, suggesting several pathogenetic mechanisms in NPSLE similar to our current understanding of the extracranial manifestations of SLE [ 6 , 15 , 16 ].…”
Section: Reviewmentioning
confidence: 75%
“…High-dose steroids are first-line treatments for active lupus flares. In other cases of neurological complications secondary to lupus, other case reports have shown that high doses for a brief duration helped alleviate neurological symptoms in patients with lupus encephalopathy [ 9 ]. The presence of very mild elevations in CRP and low titers, further points toward a non-inflammatory picture for this patient’s presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of nihilistic delusions such as the patient herself and family members being deceased along with beliefs that eating was pointless since she was already dead revealed poor insight, thus meeting ACR criterion 1 for psychosis in the presence of SLE [ 5 - 7 ]. This patient’s decline in social functioning met ACR criterion 2.…”
Section: Discussionmentioning
confidence: 99%
“…This patient’s SLE presentation was especially notable for several reasons. Neuropsychiatric manifestations as a result of SLE are rare events that occur only in around 2% of patients [ 5 , 10 ]. Lupus cerebritis is less common for a woman of 44 years of age to develop lupus cerebritis than with the pediatric and young adult populations, who are at greater stochastic risk for lupus cerebritis [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%